Implementation of Managerial Supervision in Improving School Administration Management through Monitoring and Evaluation Techniques at Mangunharjo State Elementary School - Sudyaningsih Sudyaningsih; Ine Kusuma Aryani (Green Publisher, 2024)
This study aims to determine the implementation of managerial supervision in improving educational administration management through monitoring and evaluation techniques at SD Negeri Mangunharjo in 2023. To determine the importance of implementing managerial supervision in improving education administration management through monitoring and evaluation techniques at SD Negeri Mangunharjo in 2023. To describe the implementation of managerial supervision in improving education administration management through monitoring and evaluation techniques at SD Negeri Mangunharjo in 2023. This research method uses a qualitative approach with a type of case study at SDN Mangunharjo, Adimulyo District, Kebumen Regency. The research instrument is made by the researcher himself. Activities begin with planning, implementation, evaluation and follow-up. The results obtained are documented for further submission to related parties. It can be concluded that implementing Managerial Supervision through monitoring and evaluation techniques can improve the education administration management at SD Negeri Mangunharjo in 2023. Implementing managerial supervision through monitoring and evaluation techniques is very important to improving education administration management in SD Negeri Mangunharjo.